PENGARUH STRATEGI PEMBELAJARAN PAI BERBASIS MULTIPLE INTELLIGENCES TERHADAP MINAT BELAJAR DI SMP IT INSAN KAMIL KARANGANYAR - Pratiwi, Riska Ayu; Sukari, S; Amin, Lailla Hidayatul (Al’ulum Jurnal Pendidikan Islam, 2024)
The study aims to: (1) recognizing the practice of multiple intelligence studies at the PAI lessons at Islamic Junior High School Insan Kamil Karanganyar, (2) knowing the interest of learning at the Islamic Junior High School Insan Kamil Karanganyar, and (3) learning the effects of multiple intelligence based learning with the interest of students at the Islamic Junior High School Insan Kamil Karanganyar. The study used a quantitative descriptive approach. Data collection technique used a closed angket. Data analysis technique used correlation product moment to determine the effect between variabel X and variabel Y. The result of studi is r calculate > r table, then Ha is accepted because there is an influence between the two variables. If interpreted on data of value interpretation are both variables have a medium correlation. Based on research, it can be concluded that multiple intelligence based learning has had an influence on student learning interests. By applying learning methods that quantify different kinds of intelligence, it can reduce boredom and increase student’s enthusiasm during the learning process.